From Muara Angke Port to Kali Adem Dock: The Development of Maritime Transportation in the Seribu Island - Arbiyati, Dwi Putri; Sulistiyono, Singgih Tri (Diponegoro University, 2023)
This article examines the development of maritime transportation in the Seribu Islands community concerning crossing locations and types of ships. The development of marine transportation in Seribu Island has impacted the local community since 1996. The research implemented the historical method to describe the impact of the development of the Seribu Island Port on the surrounding community and the community around Kali Adem Dock. Passenger ship crossing activities at Muara Angke Fishing Port are not very conducive because of its location adjacent to fishing activities. Ships used for transportation activities in the Seribu Island are still not seaworthy, obstructing crossing activities. As one of the icons of the capital city, the Seribu Island still needs a specific passenger ferry port. Therefore, the government has officiated Kali Adem Dock as a particular port of passenger for the Seribu Island, which is located west of Muara Angke Fishing Port. The construction of Kali Adem Dock has improved the welfare of the people of the Seribu Island. In its development, the activities in Kali Adem Dock caused several obstacles, such as rob, traffic jams, and decreased income for traders around Kali Adem Dock.